Influence of Inflammatory Disease on the Pathophysiology of Moyamoya Disease and Quasi-moyamoya Disease - MIKAMI, Takeshi; SUZUKI, Hime; KOMATSU, Katsuya; MIKUNI, Nobuhiro (Neurologia medico-chirurgica, 2019)
Moyamoya disease is a unique cerebrovascular disease that is characterized by progressive bilateral stenotic alteration at the terminal portion of the internal carotid arteries. These changes induce the formation of an abnormal vascular network composed of collateral pathways known as moyamoya vessels. In quasi-moyamoya disease, a similar stenotic vascular abnormality is associated with an underlying disease, which is sometimes an inflammatory disease. Recent advances in moyamoya disease research implicate genetic background and immunological mediators, and postulate an association with inflammatory disease as a cause of, or progressive factor in, quasi-moyamoya disease. Although this disease has well-defined clinical and radiological characteristics, the role of inflammation has not been rigorously explored. Herein, we focused on reviewing two main themes: (1) molecular biology of inflammation in moyamoya disease, and (2) clinical significance of inflammation in quasi-moyamoya disease. We have summarized the findings of the former theme according to the following topics: (1) inflammatory biomarkers, (2) genetic background of inflammatory response, (3) endothelial progenitor cells, and (4) noncoding ribonucleic acids. Under the latter theme, we summarized the findings according to the following topics: (1) influence of inflammatory disease, (2) vascular remodeling, and (3) mechanisms gleaned from clinical cases. This review includes articles published up to February 2019 and provides novel insights for the treatment of the moyamoya disease and quasi-moyamoya disease.